2017
DOI: 10.1016/j.jams.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure on Symptoms of Postoperative Ileus After Cesarean Section

Abstract: Postoperative ileus (POI) is a common complication after most abdominal surgeries including cesarean section. It is associated with longer hospitalization and increased medical costs. This study is a randomized controlled trial investigating the effect of acupressure, and low-cost noninvasive traditional treatment, on POI symptoms after cesarean section. A total of 120 patients were randomly divided into two groups; the treatment group received two sessions of acupressure (an hour after attending the women's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This finding is consistent with previous studies. 22 , 31 , 49 One possible explanation is that patients take different amounts and types of food after flatus passage, which can influence the time to have defecation passage. Future studies may measure the amount and types of food intake to examine this factor.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies. 22 , 31 , 49 One possible explanation is that patients take different amounts and types of food after flatus passage, which can influence the time to have defecation passage. Future studies may measure the amount and types of food intake to examine this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the 21 RCTs indicated that acupuncture therapies reduced time to recovery of gastrointestinal function following CRC surgery. In studies of other abdominal surgeries, acupuncture has been reported to reduce POI following gastrectomy [ 47 , 48 ] and caesarean section [ 49 ], so the effects found in this meta-analysis are not limited to surgery for CRC. With regard to type of surgery, most data were for open surgery but significant reductions in time to recovery were also evident in studies of laparoscopic surgery for CRC and surgery for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These studies evaluated a wide range of conditions including pain during laceration repair, pain after vaginal delivery, pain after cesarean section, urinary retention, volume of milk secretion, time to return of bowel function, and markers of stress after cesarean. Abadi et al79 reported that acupressure at points ST36 and LI4 resulted in the postoperative return of bowel function and showed a significant decrease in time to the presence of bowel sounds and passage of flatus compared with standard of care. For women with postpartum urinary retention after either vaginal delivery or cesarean delivery, acupuncture was equally as effective as catheterization to result in spontaneous voiding within an hour 80.…”
Section: Methodsmentioning
confidence: 99%